ChemInform Abstract: Dihydro‐β‐agarofuran Sesquiterpenes from Celastraceae Species as Antitumor‐Promoting Agents: Structure—Activity Relationship. Issue 27 (16th June 2016) - Nunez, Marvin J.; Jimenez, Ignacio A.; Mendoza, Cristina R.; Chavez‐Sifontes, Marvin; Martinez, Morena L.; Ichiishi, Eiichiro; Tokuda, Ryo; Tokuda, Harukuni; Bazzocchi, Isabel L.
Abstract: Five dihydro‐β‐agarofuran sesquiterpenes, chiapene A (Ia), chiapene B (Ib), chiapene C (II), chiapene D (III), and chiapene E (IV) are isolated from Maytenus chiapensis and tested for their inhibitory effects on Epstein—Barr virus early antigen activation.